Vitamin D serum level predicts stroke clinical severity, functional independence, and disability—A retrospective cohort study - Alharbi, Abdullah R.; Alali, Amer S.; Samman, Yahya; Alghamdi, Nouf A.; Albaradie, Omar; Almaghrabi, Maan; Makkawi, Seraj; Alghamdi, Saeed; Alzahrani, Mohammad S.; Alsalmi, Mohammed; Karamyan, Vardan T.; Al Sulaiman, Khalid; et al. (Frontiers in Neuroscience, 2022)
Background: Stroke is a leading cause of mortality and disability and one of the most common neurological conditions globally. Many studies focused on vitamin D as a stroke risk factor, but only few focused on its serum level as a predictor of stroke initial clinical severity and recovery with inconsistent results. The purpose of this study was to assess the relationship between serum vitamin D levels and stroke clinical severity at admission and functional independence and disability at discharge in Saudi Arabia. Methodology: A retrospective cohort study of adult ischemic stroke patients who had their vitamin D tested and admitted within seven days of exhibiting stroke symptoms at King Abdulaziz Medical City-Jeddah, Saudi Arabia. Based on vitamin D level, the patients were categorized into normal (25(OH)D serum level ≥75nmol/L), insufficient (25(OH)D serum level is 50-75 nmol/L), and deficient(25(OH)D serum level ≤50nmol/L). The primary outcome was to assess vitamin D serum level on ischemic stroke patients’ clinical severity at admission, and functional independence at discharge. The National Institute of Health Stroke Scale (NIHSS) was used to assess the clinical severity, whereas modified Rankin scale (mRS) was used to assess functional independence and disability. Results: The study included 294 stroke patients, out of 774, who were selected based on the inclusion and exclusion criteria. The mean age of the participants was 68.2 ±13.4 years, and 49.3% were male. The patients’ distribution among the three groups based on their vitamin D levels are: normal (n=35, 11.9%), insufficient (n=66, 22.5%), and deficient (n=196, 65.6%). After adjusting for potential covariates, regression analysis found a significant inverse relationship of NIHSS based on 25(OH)D serum level (beta coefficient: -0.04, SE: 0.01, p=0.003). Patients with deficient serum vitamin D level also had significantly higher odds of worse functional independence in mRS score (OR: 2.41, 95%CI: (1.13 – 5.16), p=0.023) when compared to participants with normal vitamin D level. Conclusion: Low vitamin D levels were associated with higher severity of stroke at admission and poor functional independence and disability at discharge in patients with acute ischemic stroke. Further randomized clinical and interventional studies are required to confirm our findings.